Integrated coffee sales standard: IPSR Innovation Profile - Calero, A.; Minot, Nicholas; Wiegel, Jenny; Reyes, Byron; Ceballos, Federico; Colindres, Mirian (CGIAR System Organization, 2024)
Interlinking extension and coffee markets through a novel and transparent standard for coffee sales to improve vertical coordination, positively impacting farm productivity, coffee quality, and price transmission. An app is used to communicate the quality test results to farmers. Integrating technical assistance with coffee sales by quality and weight is new to Honduras’s competitive and fragmented coffee supply chains. The innovation bundle would be demanded, monitored by exporters, and implemented by intermediaries. The traceability scheme will also facilitate compliance with the (EU) regulations on zero deforestation and child-labor-free agricultural supply chains.